The Effect of Green Human Resource Management on Employee Eco-Friendly Behaviour, Employee Environment-Friendly Response And Organizational Sustainability: An Empirical Study Concerning IT Industry in Hyderabad Metro (Global Journal of Management and Business Research, 2022)
The literature on green human resource management and its impact on employee eco- friendly behaviour, employee environment-friendly response, and organizational sustainability is scarce and rarely explored by researchers. This empirical study reports how an employee's eco-friendly behaviour, employee environment-friendly response through green human resource management enhances the organizational sustainability and employees' green behaviour. Organizational sustainability is a multidimensional concept that embodies social, environmental and economic objectives. The results indicate that green human resource management enhances employee eco-friendly behaviour, and employee environment-friendly response. A statistically significant impact of green human resource management on organizational sustainability was observed. The data were analyzed using the partial least square structural equation modeling (PLS-SEM). All three variables are statistically significant and predict organizational sustainability. A structured undisguised questionnaire was used to collect the data for this empirical study, publishing the questionnaire on google forms and providing a link to 5000 information technology employees. The 984 responses received and 924 valid responses were used and subjected to PLS-SEM analysis. This study recommends that the information technology policymakers should consider incorporating green human resource policies for green organizations and promote organizational sustainability.
Keywords: green human resource management; eco-friendly behaviour; organizational commitment; organizational sustainability